Pengaruh Citra Merek, Kualitas Produk, dan Harga Terhadap Loyalitas Generasi Z Pengguna Eiger di Bojonegoro - M.Fatkhur Roziq; Martha Laila Arisandra (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the influence of brand image, product quality, and price on the loyalty of Generation Z consumers using Eiger products in Bojonegoro. The research applies a quantitative approach using a survey method involving 100 respondents who have previously purchased and used Eiger products. Primary data were collected through questionnaires distributed to respondents and then analyzed using multiple linear regression analysis. The findings reveal that brand image, product quality, and price simultaneously have a positive and significant effect on consumer loyalty. Partially, product quality shows the most dominant influence on loyalty, followed by brand image and price. These results indicate that Generation Z consumers tend to prioritize product durability, design, functionality, and overall quality when deciding to repurchase Eiger products. In addition, a strong brand image and competitive pricing also contribute significantly to maintaining customer loyalty. Therefore, improving product quality, strengthening brand perception, and setting prices that match consumer expectations are considered important strategic steps for increasing long-term loyalty among Generation Z consumers in Bojonegoro.